Efektivitas Model Pembelajaran Sejarah : Problem Solving untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Kelas XI - Putri Dwi Febriyanti; Agi Ma’ruf Wijaya; Ilfiana Firzaq Arifin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study was to illuminate how effective the history learning model based on problem solving is to improve students' critical thinking skills in class XI. This study used Classroom Action Research (CAR), which was carried out in two cycles. Planning, implementation, observation, and reflection are part of each cycle. There were 24 class XI students who were the subjects of the study. Data were collected by conducting a critical thinking ability test and observing the learning process. The results showed that students' critical thinking skills increased significantly from cycle I to cycle II. Their test scores increased from 58,33% in cycle I to 83,33% in cycle II, and observations showed that students were more involved in learning activities.